Mixtures of Algal Oil and Terrestrial Oils in Diets of Tiger Puffer (Takifugu rubripes) - Lu Zhang; Haoxuan Li; Ziling Song; Qingyan Gao; Chenchen Bian; Qiang Ma; Yuliang Wei; Mengqing Liang; Houguo Xu (Animals)
The n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFAs) have a key role in maintaining fish growth and health. However, fish oil (FO), the main source of n-3 LC-PUFAs, is in relative shortage due to the rapid development of the aquaculture industry. In this study, we investigated the efficacy of replacing fish oil with mixtures of algal oil (AO) from Schizochytrium sp. and terrestrially sourced oils (animal oil poultry oil (PO) or vegetable oil rapeseed oil (RO)) in the diets of juvenile tiger puffer (average initial body weight 23.8 ± 1.51 g). An 8-week feeding trial was conducted using three experimental diets: a control diet containing 6% added FO (control FO-C) and two diets with 3% AO + 3% PO or RO (groups AO+PO and AO+RO, respectively), replacing FO. Each diet was fed to triplicate tanks with 25 fish in each tank. The weight gain, feed conversion ratio, body composition, and serum biochemical parameters were not significantly different among the three groups, except that the AO+PO group had a significantly lower muscle lipid content than the other two groups. The AO-added diets significantly increased the DHA content in whole fish, muscle, and liver samples but significantly reduced the EPA content. The oil mixture treatments significantly increased the contents of monounsaturated fatty acid (MUFA) but significantly decreased the contents of saturated fatty acids (SFAs) in the liver and whole fish samples. However, the MUFA and SFA contents in the muscle samples were not significantly different among the dietary groups. The diets with oil mixtures did not affect the hepatic histology but tended to result in the atrophy of intestinal villi. The treatment diets downregulated the hepatic gene expression of proinflammatory cytokines (il-1β and tnf-α) and the fibrosis marker gene, acta2. However, the AO+PO diet inhibited the intestinal gene expression of the tight junction protein, claudin 18. In the muscle, the treatment diets upregulated the expression of genes related to cell differentiation and apoptosis (myod, myog, myf6, myf5, bcl-2, and bax). In conclusion, Schizochytrium sp. oil in combination with terrestrial oils (poultry oil or rapeseed oil) can be an effective alternative to fish oil in the diets of tiger puffer, but the mixing strategy may be better modified in consideration of intestinal health.